Impact of Terrorism and the Role of Media in Islamophobia Propaganda (Systematic Literature Review) - Anadza Iron Albaroza; Rizky Bagastian; Anita Anita; Iradhad Taqwa Sihidi (Budapest International Research and Critics University, 2022)
The terrorist movement has often been heard of, both in Indonesia and from other parts of the country. Several studies discuss whether terrorism is included in the impact of globalization where the movement quickly spreads with globalization and becomes a form of transnational movement that eventually enters other countries and develops rapidly and promptly distributes ideas to existing ones. First, identify the article. The article was taken from the publications of various authors using a database from Scopus. The next step is to enter the keyword